How Does Digital Finance Affect People's Income: Evidence from China. (17th May 2022) - Wang, Tingting; Ji, Cheng
Abstract : Using data from the China Family Panel Studies (CFPS) from 2010 to 2018 and the Peking University Digital Financial Inclusion Index from 2011 to 2018, this research explores the effect of digital financial development on residents' income and the channels of influence. The findings suggest that the growth of digital financial services has a significant and favourable influence on citizens' income. Furthermore, digital financial development benefits rural populations, low-skilled workers, and individuals working in basic industries the most. The extension of inhabitants' employment space, better access to credit, and ease of access to information online are the major ways that digital financial development influences their income. In particular, the expansion of employment space has a greater positive impact on the low-skilled labor force, rural residents, and those in primary and secondary industries, while access to information is more likely to explain the increase in income of urban residents, and credit has an advantage in promoting income growth for the low-skilled laborers and those in traditional industries.